Online travel survey response rates and researcher ethnicity - Pan, B.; Smith, W.; Litvin, S.; Woodside, Arch (John Wiley & Sons, 2018)
© 2018 John Wiley & Sons, Ltd. This paper documents a United States-based experiment that tested response rates to an online travel survey request. The results of the experiment revealed a dramatically lower rate of response to requests sent by a researcher with an ethnically Chinese-name than to an identical request from a researcher with a Western-name. The importance of this study is evident to tourism practitioners and academic tourism researchers who so often rely upon survey-based research. Recommendations for overcoming ethnic bias are provided.